Occurrence of Chiorchis fabaceus (Trematoda: Cladorchiidae) in a wild Antillean manatee (Trichechus manatus manatus): New parasitological data for this imperilled sirenian (2024)
ABSTRACT: Parasites impact wildlife populations and ecosystem health, thereby demanding regular monitoring. As part of the national conservation effort to preserve the free-ranging sirenians in Colombia, a parasitological survey was conducted between 2011 and 2023 on naturally deceased Antillean manatees (Trichechus manatus manatus). A total of 17 stranded carcasses were analysed for the occurrence of parasites. Herein, trematode adult stages were recovered from the stomach, small intestine, caecum and colon of an adult male manatee and microscopically analysed. Additionally, molecular analysis was conducted based on an almost complete coding sequence of the ITS1–5.8S-ITS2, partial sequence of 18S and 28S ribosomal DNA (rDNA) genes. Phylogenetic analysis clustered the trematode sequences within Chiorchis fabaceus species, thus constituting the first adult-based sequences isolated for the species. Presented data contribute to a better understanding of the sirenian parasite diversity.